Cytoglobin expression in oxidative stressed liver during systemic chronic normobaric hypoxia and relation with HIF-1α (Faculty of Medicine Universitas Indonesia, 2014)
Background: Liver is sensitive against hypoxia and hypoxia will stabilize HIF-1α. At the same time, hypoxia will produce reactive oxygen species (ROS) which can be scavenged by Cygb. The purpose of our study is to know, if normobaric hypoxia can induce Cygb expression and its association with HIF-1α stabilization. Methods: This is an experimental study using 28 male Sprague-Dawley rats, 150-200 g weight. Rats are divided into 7 groups: control group and treatment groups that are kept in hypoxic chamber (10% O2: 90% N2) for 6 hours, 1, 2, 3, 7 and 14 days. All rats are euthanized after treatment and liver tissue are isolated, homogenized and analyzed for oxidative stress parameter, expression of Cygb and HIF-1α. Results: Expression of Cygb mRNA and protein was increased on the day-1 after treatment and reach the maximum expression on the day-2 of hypoxia treatment. But, the expression was decreased after the day-3 and slightly increased at the day-14 of hypoxia. The correlation between expression of Cygb and oxidative stress parameter was strongly correlated. Cygb mRNA, as well as protein, showed the same kinetic as the HIF-1, all increased about day-1 and day-2. Conclusion: Systemic chronic hypoxia and/or oxidative stress up-regulated HIF-1α mRNA which is correlated with the Cygb mRNA and protein expression. Cygb mRNA as well as Cygb protein showed the same kinetic as the HIF-1, all increased about day-1 and day-2 suggesting that Cygb could be under the regulation of HIF-1, but could be controlled also by other factor than HIF-1.